2017
DOI: 10.1039/c7ta03027d
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic nanostructures in a porous carbon framework significantly enhance electrocatalytic oxygen evolution

Abstract: Hybrid carbons, nickel embedded nanographites in a nitrogen-doped porous carbon structure, developed by a simplified CVD fashion, utilizing a solid state precursor, zeolitic-imidazolate-framework, lead to highly enhanced water oxidation activity over simple graphitic or porous carbon based structures alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…However, in the literature these ZIF-derived carbon structures are far from the ideal system, commonly due to inadequate processing methods. The carbonization of ZIFs is frequently carried out at elevated temperature, beyond 600 C and up to 1100 C. 3,4,16,[20][21][22][23][24][25][26][27][28] This carbonization temperature is a critical parameter to control the respective elemental concentration in the targeted M-N-C system. The hightemperature treatment of the ZIF precursors usually induces a low catalyst yield with a mass loss of >70 wt%, mostly due to the dissociation of the highly desirable active -N-C, or hydrocarbon content.…”
mentioning
confidence: 99%
“…However, in the literature these ZIF-derived carbon structures are far from the ideal system, commonly due to inadequate processing methods. The carbonization of ZIFs is frequently carried out at elevated temperature, beyond 600 C and up to 1100 C. 3,4,16,[20][21][22][23][24][25][26][27][28] This carbonization temperature is a critical parameter to control the respective elemental concentration in the targeted M-N-C system. The hightemperature treatment of the ZIF precursors usually induces a low catalyst yield with a mass loss of >70 wt%, mostly due to the dissociation of the highly desirable active -N-C, or hydrocarbon content.…”
mentioning
confidence: 99%
“…The ZIF‐8 exhibits a negligible OER activity compared with a high current response from ZIF‐67. A potential of approximately 1.72 V (vs. reversible hydrogen electrode (RHE) with onset potential being close to 1.6 V) to reach an impressive benchmark current density of 10 mA cm −2 in ZIF‐67 is comparable to many of the carbon‐based nanostructures reported [35, 37–39] …”
Section: Resultsmentioning
confidence: 88%
“…The catalytic performance of CoP@HPC−T showed that carbonization temperature had a significant effect on their catalytic activity. The excellent catalytic performance of CoP@HPC‐500 benefited from the complete phosphorization, while the reduction of CoP@HPC‐T activity may be attributed to the reduction tendency of phosphorisation and the increase of particle size due to the higher temperatures induced metal aggregation . Comparatively, to further confirm the effect of phosphorization, the hydrolytic of AB by using the Co@HPC‐500 was also performed.…”
Section: Resultsmentioning
confidence: 98%